Correlation between the DJSI Chile and the financial indices of Chilean companies - Karime Chahuán-Jiménez (International Journal of Financial Studies, 2020)
The Dow Jones Sustainability Index Chile (DJSI Chile) is made up of leading sustainability companies that are investing great effort into sustainable management. This study correlates the DJSI Chile with the financial indices (return on equity (ROE), return on assets (ROA), market value, earnings, and leverage) of companies that belong to the General Stock Price Index (IGPA) in Chile. The methodology used was quantitative, considering Chilean companies in the IGPA, including companies belonging to the DJSI Chile, applying a normality and correlation test based on the results. In conclusion, the study shows that in the results for the ROE, ROA, and leverage variables, there is no positive correlation with the DJSI Chile. However, the DJSI Chile is correlated with market value (for approximately 80% of the companies), and with earnings, there is a slightly higher correlation for the companies that belong to the DJSI Chile than for the remaining companies in the IGPA, thus if there exists a correlation between the DJSI Chile index and the variables market value and earnings, the index enables the prediction of those financial variables or predicts the finance indices (value market and earnings) of the companies that make up the DJSI Chile basing in the DJSI Chile index.
Keywords: G14; G49; D53; 330; integrated reporting; sustainability reporting; DJSI Chile; financial indices; financial markets